Peran Teknologi Informasi pada Humas Lembaga Pendidikan - Dewi Andriani; Ulum Wahyu Febri Anggraini (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2022)
This study aimed to determine the role of information technology in the public relations of educational institutions. The function of public relations in educational institutions is very important. Because with good public relations, educational institutions can continue their existence so that they can use it as a way to make their institutions exist and have a good image in society. Parts of the internet used by public relations in connecting with the public are websites, electronic mail, online bulletins, instant messages, blogs, and social networks. Of course, apart from using the internet, public relations work is still supported by the use non internet media and also face to face. The use of any media does not alter the fundamental function of public relations as a link between organizations with stakeholders, that media as supporting facilities of public relations work.Keyword : Information technology, public relations, education